(untitled) - McComb, Gordon (Blue Ridge Summit, PA., 1990)
Electronics wizard Gordon McComb has assembled more than 55 practical projects ranging in difficulty from a simple Jacob's Ladder to a complete laser light show. Whether you're experienced or not, you'll find plenty here to keep you busy honing your workbench skills.
Keywords: Electronics,Điện tử học; Amateurs' manuals,Sách dành cho người nghiệp dư